Use of Indirect Speech Acts in Business Correspondence - Pešoutová, Nikola (Univerzita Pardubice, 2015)
This bachelor thesis deals with the occurrence and usage of indirect speech acts in business correspondence. The paper aims to examine the illocution functions of the utterances, their degree of politeness and the interpretation of their meanings. Another point is to examine their communication functions and the influence the utterances make on their addressees. The paper is divided into a theoretical section, purpose of which is to investigate the topic of indirect speech acts, and a practical section, in which the aspects discussed in theory are put into practice through exploring a sample of business correspondence.
Užití nepřímých řečových aktů v obchodní korespondenci
Keywords: meaning; indirect speech acts; indirectness; illocution function; business correspondence; politeness; modal verbs; modifiers; význam; nepřímé řečové akty; nepřímost; ilokuční funkce; obchodní korespondence; zdvořilost; modální slovesa; umocňovače